PENGEMBANGAN MEDIA PAPAN PERJALANAN (BILBUL) MATERI OPERASI BILANGAN BULAT PENJUMLAHAN DAN PENGURANGAN DI KELAS IV SD NEGERI 107432 BANGUN PURBA TENGAH - Iga Marisa Sembiring; Sujarwo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
subtraction integer operations in class IV to help understand mathematics learning material and improve student learning outcomes. In this research, researchers used the learning media development method with the ADDIE approach model. The method used in this research uses a development model with the ADDIE approach. The research subjects of this research are media expert validators and material experts, namely UMN Al Washliyah lecturers. The research object is the development of travel board media (Bilbul) on integer operation material to help students in learning mathematics on the operation of saying round in class IV at SD Negeri 107432 Bangun Purba Tengah. The aim of developing Travel Board media in learning addition and subtraction integer operations in class IV is to help understand mathematics learning material and improve student learning outcomes. Based on the results of calculations. from material experts and media experts, the assessment results from material experts were 90%, and the calculation results from media experts were 86%. If the percentage obtained reaches 81% to 100%. So the Travel Board media is categorized as "very feasible". From these calculations, the percentages obtained are 90% and 86%, so the Travel Board media is declared very suitable for use.